The impact of asthma on COVID-19 disease severity in children and adolescents. (3rd June 2023) - Robbins, Emily; Daoud, Steven; Demissie, Seleshi; James, Pushpom
Abstract: Background: Atopy and allergic asthma have been found to be protective against coronavirus disease (COVID-19) in adults but have not been studied in children. Objective: To identify whether children and adolescents with asthma had less severe disease and lower morbidity from COVID-19 than their counterparts without asthma. Methods: This was a retrospective chart review from March 1, 2020, through January 31, 2021. Charts were eligible for inclusion if patients were over 6 years of age and below 20 years of age and tested positive for COVID-19 by PCR or antigen testing or were COVID-19 antibody positive when they presented to the emergency department (ED). Patients were grouped according to disease severity and divided into two groups, those with asthma and those without. A total of 1, 585 patients were included—1, 492 without asthma and 93 with asthma. Results: Children and adolescents with asthma are less likely to be seen in the ED for COVID-19–related disease (p value< 0.0001, but if they presented to the ED, they were significantly more likely to be hospitalized, require oxygen, and have more severe forms of COVID-19 than children and adolescents without asthma (p value< 0.0001). Conclusions: Children and adolescents with asthma, though less likely to be seen in ED with COVID-19, were more likely to have severe disease than patients without asthma, once they presented to the ED.